Cultures in collision and conversation : essays in the intellectual history of the Jews - Berger, David, 1943- (Boston : Academic Studies Press, 2011)
In Cultures in Collision and Conversation, David Berger addresses three broad themes in Jewish intellectual history: Jewish approaches to cultures external to Judaism and the controversies triggered by this issue in medieval and modern times, the impact of Christian challenges and differing philosophical orientations on Jewish interpretation of the Bible, and Messianic visions, movements, and debates from antiquity to the present. These essays include a monograph-length study of Jewish attitudes toward general culture in medieval and early modern times, analyses of the thought of Maimonides and Nahmanides, an assessment of the reactions to the most recent messianic movement in Jewish history, and reflections on the value of the academic study of Judaism. --From publisher's description.
The cultural environment : challenge and response. Identity, ideology, and faith : some personal reflections on the social, cultural, and spiritual value of the academic study of Judaism ; Judaism and general culture in medieval and early modern times ; How die Nahmanides propose to resolve the Maimonidean controversy? ; Miracles and the natural order in Nahmanides ; Polemic, exegesis, philosophy, and science : reflections on the tenacity of Ashkenazic modes of thought ; Malbim's secular knowledge and his relationship to the spirit of the Haskalah ; The uses of Maimonides by twentieth-century Jewry ; The Institute for Jewish Studies on its eightieth anniversary -- Interpreting the Bible. "The wisest of all men" : Solomon's wisdom in medieval Jewish commentaries on the Book of Kings ; On the morality of the patriarchs in Jewish polemic and exegesis -- Yearning for redemption. Three typological themes in early Jewish Messianism : Messiah son of Joseph, rabbinic calculations, and the figure of Armilus ; Some ironic consequences of Maimonides' rationalist approach to the Messianic age ; Sephardic and Ashkenazic Messianism in the Middle Ages : an examination of the historiographical controversy ; Maccabees, Zealots, and Josephus : the impact of Zionism on Joseph Klausner's history of the second temple ; The fragility of religious doctrine : accounting for orthodox acquiescence in the belief in a second coming -- Epilogue. The image of his father : on the twenty-fifth anniversary of the death of Hadoar Author Isaiah Berger.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Judaism -- Relations; Intercultural communication -- Religious aspects -- Judaism; Judaism -- History; Jews -- History; Jews -- Intellectual life; Messianic era (Judaism); RELIGION -- Judaism -- Theology; PHILOSOPHY / Religious; Electronic books